EXPERIMENTAL STRUCTURE FOR EVALUATION OF BRACKISH WATER USE IN LETTUCE HYDROPONIC PRODUCTION - Soares, Tales Miler; Duarte, Sergio Nascimento; França e Silva, Ênio Farias de; Mélo, Ralini Ferreira; Jorge, Cristiano de Andrade; Oliveira, Áureo Santana de (IRRIGA, 2009)
EXPERIMENTAL STRUCTURE FOR EVALUATION OF BRACKISH WATER USE IN LETTUCE HYDROPONIC PRODUCTION Tales Miler Soares; Sergio Nascimento Duarte; Ênio Farias de França e Silva; Ralini Ferreira Mélo; Cristiano de Andrade Jorge; Áureo Santana de Oliveira Departamento de Engenharia Rural, Escola Superior de Agronomia Luiz de Queiroz, Universidade de São Paulo, talesmiler@bol.com.br 1 ABSTRACT Despite the usual utilization of hydroponic systems in agricultural research, such management systems do not always use the same techniques commercially feasible, leading to few pragmatic results for farmers. This is an important observation because inBrazilthe majority of hydroponic vegetable production uses the nutrient film technique (NFT). Therefore, research must be carried out in NFT systems to find out its contribution on horticulture and environmental protection studies. The salt tolerance of plants may be greater in hydroponics systems than it turns out to be under conventional soil-based systems. The possibility of use of brackish water in soilless cultivations can be seen as a new perspective on Brazilian semi-arid agriculture, besides contributing to the improvement of the agricultural environment safety. In order to test the hypothesis of a positive effect of high irrigation frequency of hydroponic system on the salt tolerance of plants, a structure with 40 experimental units was constructed . Each experiment unit was designed to represent a hydroponic NFT system. This paper presents and describes the experimental structure built. Preliminary findings from lettuce cultivation suggest that the experimental structure is feasible for scientific investigations. KEY WORDS: soilless, salinity, electrical conductivity, vegetables, NFT. SOARES, T.M.; DUARTE, S.N.; SILVA, E.F.F.; MÉLO, R.F.; JORGE, C.A.; OLIVEIRA, A.S. ESTRUTURA EXPERIMENTAL PARA AVALIAÇÃO DO USO DE ÁGUAS SALOBRAS NA PRODUÇÃO HIDROPÔNICA DE ALFACE 2 RESUMO Apesar do uso da hidroponia ser comum em pesquisas, nem sempre essas adotam as mesmas técnicas comercialmente viáveis, o que leva a resultados pouco pragmáticos aos agricultores. Essa é uma observação importante, pois, no Brasil na maioria dos cultivos hidropônicos comerciais de hortaliças folhosas se utiliza a técnica do fluxo laminar de nutrientes (NFT). Nesse sentido, as pesquisas devem ser conduzidas no sistema NFT para demonstrar sua contribuição em horticultura e estudos de proteção ambiental. A tolerância das culturas à salinidade deve ser maior em sistemas hidropônicos do que em sistemas convencionais de cultivo. A possibilidade de uso de águas salobras na hidroponia pode contribuir para uma nova perspectiva à agricultura do semi-árido brasileiro, colaborando, inclusive, para uma maior segurança ambiental. A alta freqüência da irrigação em sistemas hidropônicos aumenta a tolerância das plantas à salinidade. Para testar a hipótese de um efeito positivo da alta freqüência de irrigação dos sistemas hidropônicos sobre a tolerância à salinidade, foi construída uma estrutura com 40 parcelas. Cada parcela foi projetada para representar individualmente um sistema hidropônico NFT. No presente artigo é apresentada e descrita a estrutura experimental montada. Resultados preliminares com a cultura da alface indicam que a estrutura experimental é viável para investigações científicas. UNITERMOS: hidroponia, salinidade, condutividade elétrica, hortaliças, NFT.